Comparative Analysis of Biological Properties of Large-Scale Expanded Adult Neural Crest-Derived Stem Cells Isolated from Human Hair Follicle and Skin Dermis - Roman G. Vasyliev; Olga S. Gubar; Inna M. Gordiienko; Larisa S. Litvinova; Anzhela E. Rodnichenko; Valeria V. Shupletsova; Alona V. Zlatska; Kristina A. Yurova; Natalia M. Todosenko; Veronika E. Khadzhynova; Mariia V. Shulha; Svitlana N. Novikova; et al. (Stem Cells International)
Introduction. The adult neural crest-derived stem cells (NCSCs) have significant perspectives for use in regenerative medicine. The most attractive sources for adult NCSC isolation are the hair follicles (HF) and skin dermis (SD) because of easy access and minimally invasive biopsy. The aim of this study was to compare the biological properties of HF- and SD-derived NCSCs after their large-scale expansion. Methods. The conventional explant method was used to obtain HF NCSCs. For the isolation of SD NCSCs, a new combined technique consisting of preplating and subsequent culturing in 3D blood plasma-derived fibrin hydrogel was applied. The studied cells were characterized by flow cytometry, ICC, qPCR, Bio-Plex multiplex assay, and directed multilineage differentiation assays. Results. We have obtained both adult SD and HF NCSCs from each skin sample (n=5). Adult SD and HF NCSCs were positive for key neural crest markers: SOX10, P75 (CD271), NESTIN, SOX2, and CD349. SD NCSCs showed a higher growth rate during the large-scale expansion compared to HF NCSCs (p<0.01). Final population of SD NCSCs also contained more clonogenic cells (p<0.01) and SOX10+, CD271+, CD105+, CD140a+, CD146+, CD349+ cells (p<0.01). Both HF and SD NCSCs had similar gene expression profiling and produced growth factors, but some quantitative differences were detected. Adult HF and SD NCSCs were able to undergo directed differentiation into neurons, Schwann cells, adipocytes, and osteoblasts. Conclusion. The HF and SD are suitable sources for large-scale manufacturing of adult NCSCs with similar biological properties. We demonstrated that the NCSC population from SD was homogenous and displayed significantly higher growth rate than HF NCSCs. Moreover, SD NCSC isolation is cheaper, easier, and minimally time-consuming method.